Comparison of entamoeba histol ytica antibodies and lectin antigen- levels in the sera of patients suspected with amoebic liver abscess in HUSM - Abdul Wahab, Wan Nor Azilah @ Wan Nor Amilah Wan (2007)
Background: Indirect haemagglutination assay (IHA) is one of the most widely used methods to detect Entamoeba histo/ytica antibodies. In an amoebiasis endemic area such as Kelantan, interpretation of a positive IHA result can be problematic due to the high background antibody levels. The TechLab E. histo/ytica II ELISA is a commercial kit for detection of specific GallGalNAc lectin antigen in stool samples, and has been reported to be able to detect the antigen in serum samples from patients with amoebic liver abscess (ALA). Thus in this study, the usefulness of the TechLab E. histo/ytica II ELISA was compared with IHA in the diagnosis of ALA. The objective of the study is to determine and compare the level of antibodies by IHA and the presence of Gai/GalNAc ledin antigens by ELISA in the sera of suspected ALA patients. Method: This is a cross sectional study involving 43 clinical or suspected ALA patients who were admitted to the surgical ward, Hospital USM, Kelantan. The diagnosis of ALA was established based on clinical symptoms and signs, ultrasound and/or CT scan results. Clinical data of the patients were reviewed . from the hospital files. The serum specimens were obtained from the patients and tested with IHA and ELISA methods according to the manufacturers instructions. Results: The majority of patients in this study were Malays, males were affected more than females and the' majority Was in the age group of 20-59 years old. Three most common clinical signs and symptoms on presentation were fever, abdominal pain and hepatomegaly. Majority of patients were found to have single abscess located at the right lobe of liver and with the presence of leucocytosis. Of all 43 patients, 76.7% was IHA positive and only 2.3% was ELISA positive. The agreement between IHA for antibody detection and ELISA for lectin antigen detedion was poor. There was no correlation between ELISA results and IHA of different antibody titers. The complication of ALA was pleural effusion occurring in 30.2% of the patients. Conclusion:Based on the findings, the ELISA method used in this study was not sensitive in detecting amoebic antigen in serum samples from ALA patients. In addition, the results of ELISA test did not correlate with the IHA antibody titers. Therefore, the TechLab E. histolytica II ELISA was found not to be a useful test for serological diagnosis of AlA in HUSM.